The Role of Green Accounting in Islamic Finance: Opportunities and Challenges in the Era of ESG - Abdul Khaliq; Sahrullah; Kahar (www.amertainstitute.com, 2024)
Green accounting is gaining recognition as a vital tool for promoting environmental sustainability, particularly within Islamic finance, which emphasizes ethical and responsible economic practices. This study investigates the integration of green accounting principles into Islamic financial institutions, analyzing their potential role in addressing Environmental, Social, and Governance (ESG) concerns and advancing global sustainability objectives. Using a mixed-methods approach, the research combines literature reviews, case studies of green sukuk implementations, interviews with financial practitioners, and survey analysis of Islamic financial institutions. The findings highlight several opportunities, including the natural alignment of Islamic finance principles with ESG objectives and the success of instruments such as green sukuk in financing sustainable projects. Green accounting enhances transparency and accountability in environmental reporting, boosting stakeholder trust and institutional credibility. However, significant challenges remain, such as the lack of standardized frameworks for green accounting tailored to Islamic finance, limited expertise among professionals, and resistance to adopting new practices due to perceived costs and complexities. The study emphasizes the need for capacity-building initiatives, regulatory support, and collaboration among stakeholders to overcome these barriers. While the research provides valuable insights into the integration of green accounting in Islamic finance, limitations include the geographic scope of the case studies, data accessibility, and the emerging nature of the field, making longitudinal assessments challenging. Despite these constraints, the research underscores that the adoption of green accounting is not only feasible but also critical for positioning Islamic finance as a key driver of environmental sustainability in the era of ESG and Sustainable Development Goals (SDGs).